2022
DOI: 10.3390/cancers14102419
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pre-Operative Brain Imaging in Patients with NSCLC Stage I: A Retrospective, Multicenter Analysis

Abstract: Background: Lung cancer is the worldwide leading oncological cause of death in both genders combined and accounts for around 40–50% of brain metastases in general. In early-stage lung cancer, the incidence of brain metastases is around 3%. Since the early detection of asymptomatic cerebral metastases is of prognostic value, the aim of this study was to analyze the incidence of brain metastases in early-stage lung cancer and identify possible risk factors. Methods: We conducted a retrospective multicentric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…8–11 While there are ongoing clinical studies investigating the role of BM screening in HR+, HER2+, TN, and inflammatory breast cancers, to date data are conflicting and require further investigation. 44 , 45 Due to a relative paucity of data, further clinical trials incorporating molecular data into screening guidelines for BM are necessary to rigorously evaluate the benefits of molecular-based BM screening recommendations. The absence of guidelines for follow-up imaging for asymptomatic breast cancer and NSCLC patients after an initial negative MRI highlights the need for more research in this area, especially as many patients who are initially negative for BM go on to develop BM later in the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8–11 While there are ongoing clinical studies investigating the role of BM screening in HR+, HER2+, TN, and inflammatory breast cancers, to date data are conflicting and require further investigation. 44 , 45 Due to a relative paucity of data, further clinical trials incorporating molecular data into screening guidelines for BM are necessary to rigorously evaluate the benefits of molecular-based BM screening recommendations. The absence of guidelines for follow-up imaging for asymptomatic breast cancer and NSCLC patients after an initial negative MRI highlights the need for more research in this area, especially as many patients who are initially negative for BM go on to develop BM later in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“… 44 That said, studies of stage I NSCLC undergoing brain imaging with CT and/or MRI prior to lung disease resection, found that the incidence of asymptomatic BM amongst these patients (1.4%–2.4%) was too low to justify routine screening. 44 , 45 As a result, preoperative brain imaging for stage II NSCLC patients undergoing surgical resection of their disease is recommended as these patients can have concurrent asymptomatic BM. 46 …”
Section: Epidemiology Molecular Characterization and Screening Guidel...mentioning
confidence: 99%
“…Рак легкого -одно из самых распространенных в мировой популяции злокачественных новообразований. В случае рака легкого около 40% всех метастазов приходится на головной мозг, которые на ранних стадиях заболевания возникают примерно у 3% пациентов [1]. Не только своевременность, но и качество диагностики напрямую влияют на выживаемость больных и качество их жизни.…”
Section: Introductionunclassified